TGF-β signaling mediates endothelial to mesenchymal transition (EndMT) during vein graft remodeling - Cooley, Brian C. (2014)
Veins grafted into an arterial environment undergo a complex vascular remodeling process. Pathologic vascular remodeling often results in stenosed or occluded conduit grafts. Understanding this complex process is important for improving the outcome of patients with coronary and peripheral artery disease undergoing surgical revascularization. Using in vivo murine cell lineage-tracing models, we show that endothelial-derived cells contribute to neointimal formation through endothelial to mesenchymal transition (EndMT), which is dependent upon early activation of the Smad2/3-Slug signaling pathway. Antagonism of TGF-β signaling by TGF-β neutralizing antibody, shRNA-mediated Smad3 or Smad2 knockdown, Smad3 haploinsufficiency, or endothelial cell-specific Smad2 deletion resulted in decreased EndMT and less neointimal formation compared to controls. Histological examination of postmortem human vein graft tissue corroborated the changes observed in our mouse vein graft model, suggesting that EndMT is operative during human vein graft remodeling. These data establish that EndMT is an important mechanism underlying neointimal formation in interpositional vein grafts, and identifies the TGF-β/Smad2/3-Slug signaling pathway as a potential therapeutic target to prevent clinical vein graft restenosis.